2012
DOI: 10.1186/1471-2288-12-146
|View full text |Cite
|
Sign up to set email alerts
|

Intervention dose estimation in health promotion programmes: a framework and a tool. Application to the diet and physical activity promotion PRALIMAP trial

Abstract: BackgroundAlthough the outcomes of health promotion and prevention programmes may depend on the level of intervention, studies and trials often fail to take it into account. The objective of this work was to develop a framework within which to consider the implementation of interventions, and to propose a tool with which to measure the quantity and the quality of activities, whether planned or not, relevant to the intervention under investigation. The framework and the tool were applied to data from the diet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…The implications of these uncertainties were highlighted by a recent systematic review and metaregression that found that the dose of a behavioral intervention was unrelated to effect size on child weight outcomes [9]. The relationship between dose and weightrelated outcomes is unclear partially because of variability in how behavioral intervention dose is categorized and quantified [10,11]. The NIH Treatment Fidelity Framework distinguishes between "how an intervention was intended to be delivered" vs. "how well providers adhere to the intended treatment, including information about actual dose and content delivered" [12].…”
Section: Introductionmentioning
confidence: 99%
“…The implications of these uncertainties were highlighted by a recent systematic review and metaregression that found that the dose of a behavioral intervention was unrelated to effect size on child weight outcomes [9]. The relationship between dose and weightrelated outcomes is unclear partially because of variability in how behavioral intervention dose is categorized and quantified [10,11]. The NIH Treatment Fidelity Framework distinguishes between "how an intervention was intended to be delivered" vs. "how well providers adhere to the intended treatment, including information about actual dose and content delivered" [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wasik and colleagues [12] distinguish between implementation and intervention dose and further subdivide the latter into the amount of intervention intended, offered, and received. Legrand and colleagues [7] provide an equation to calculate dose that involves measuring delivery quantity and quality and participation quantity and quality. Finally, Cheadle and colleagues [13] introduce the concept of ‘population dose’ which is defined as a product of the reach of an intervention and the strength of the effect (estimated as the effect on each person reached by the intervention).…”
Section: Introductionmentioning
confidence: 99%
“…Process data, including quantitative and qualitative measures of participation and intervention delivery, was intended for estimating an intervention dose [37] . In health promotion programs, particularly those conducted within the framework of controlled trials, the level to which interventions are implemented must be considered when interpreting outcomes.…”
Section: Methodsmentioning
confidence: 99%